A Study Of Parameters Influencing Direct Coal Firing Of Grate-Kilns - B. P. Faulkner (Society for Mining, Metallurgy & Exploration, 1977)
In 1974, Allis-Chalmers, in corporation with several iron ore operating companies, began to evaluate direct firing of coal in the GRATE-KILN System. Several coals were ground at the Allis-Chalmers Process Research and Test Center and shipped to Cleveland Cliff's pilot plant near Negaunee, Michigan, where they were used as fuel to pelletize Empire magnetite concentrates in the CCI pilot-scale grate kiln. Pilot plant tests were sufficiently favorable to warrant testing in a commercial-scale pelletizing plant. These tests were conducted at the Empire Mine in the late summer and fall of 1974 and again in the summer and early fall of 1975. In the fall of 1975, Allis-Chalmers Mining Systems Division started a program, in the Advanced Technology Center, designed to develop a laboratory test procedure for the evaluation and study of various parameters associated with the direct firing of coals in a GRATE-KILN System. The initial results of this program were presented at the 50th Annual Meeting Minnesota Section, AIME, January, 1977. This paper will briefly review the initial laboratory work and discuss the latest results obtained.